SDS PAGE OF WHOLE CELL PROTEIN, IMMUNOBLOTTING AND PROTEIN A ASSAY FOR TYPING OF STAPHYLOCOCCUS AUREUS ISOLATED ON DOGS AND CATS - Arabi, Omer H. Arabi; Mutalib, Abdul Rahim; Abdul Aziz, Saliha; Sheikh Omer, Abdul Rahman; Radu, Son (Gezira Journal of Health Sciences; Vol 4 No 1 (2008), 2008)
A total of 36 isolates of Staphylococcus aureus from hospitalised and out patient dogs and cats were typed using SDS PAGE of whole cell protein, immunoblotting and protein A assayment by ELISA test. 15/24 and 14/24 profiles were recognised using SDS PAGE and immunoblotting respectively. It is concluded that SDS PAGE of whole cell protein and immunoblotting could be used as a typing methods for the characterisation of S. aureus strains. Protein A assayment could be used for the detection of S. aureus strains in samples but could not be used to differentiate between different strains.